Game structure analysis in adolescent squash players - Wei, Chow Xiao (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
This study was aimed to determine the game structure of adolescent male squash players generally, in Under-17 Age Category (U-17), Under-19 Age Category (U-19) and between these two age categories. Fifty squash games (twelve matches) recorded in four Junior National Tournaments were analyzed to obtain the data of match duration (minutes), game duration (minutes), rallies per game, shots per rally, rally length (seconds), rest time between rallies (seconds), ball in play in minutes, ball in play in percentage (%) and work-rest ratio. Results for general game structure (where both categories had taken into account) showed the means of game duration at 8.87 minutes, number of rallies per game at 20.36, number shots per rally at 1 0.54, rally length at 16.04 seconds, time between rallies at 10.40 seconds, ball in play at 5.46 minutes or 61.77%, work-rest ratio at 1.70 and match duration at 36.15 minutes. Results showed the number of shots per rally, ball in play in minutes, ball in play in percentage, rally length, work-rest ratio being significantly higher in U-19 than in U-17. Adolescent players in U-19 possess quite similar values for rally length, number of shots per rally, rest time between rallies and ball in play in percentage when compared with adult elite squash players. Training protocol of adolescent squash players should basically follow the game structure during match-play which had been found in the study and the differences between U-17and U-19 suggest training loads should be applied differently in the mentioned categories.